Synthesis and characterization of cellulose/TiO2 nanocomposite: Evaluation of in vitro antibacterial and in silico molecular docking studies. (1st December 2020) - M.V., Arularasu; Harb, M.; Sundaram, R.
Highlights: Cellulose/TiO2 nanocomposite was prepared by co-precipitation method. XRD analysis of cellulose/TiO2 nanocomposite showed that the TiO2 impregnation did not change the cellulose structure. Improved antibacterial activities against Gram positive and negative bacteria. Antibacterial activity was attributed to the cell membrane damage and ROS generation. The docking models with negative binding energy for the cellulose/TiO2 nanocomposite imply facile and favorable association of the nanocomposite and protein. Abstract: Cellulose/TiO2 nanocomposite was synthesized using coagulation in sodium hydroxide-thiourea-urea aqueous solution medium by precipitation method. This method was accomplished green and cost-effective for the fabrication of composite nanomaterials. Structure, morphology and optical properties of the nanocomposite were characterized by X-ray diffraction, energy dispersive X-ray spectroscopy, field emission scanning electron microscopy, transmission electron microscopy, and ultraviolet diffuse reflectance spectra respectively. XRD results showed the anatase structure of TiO2 while FESEM micrograph showed evidence of particle size ranging from 20 to 40 nm for cellulose/TiO2 nanocomposite. The Fourier transfer infrared spectroscopy investigation reveals that the TiO2 is bound to hydroxyl groups to the cellulose by hydrogen bonding. The optical energy bandgap is found to be 2.71 eV for nanocomposite from the UV-DRS. The mechanical strength of the composites gently escalated with the addition of TiO2 nanoparticles into cellulose polymer matrix. Cellulose/TiO2 nanocomposite was screened for their in vitro antibacterial activity against Staphylococcus aureus and Escherichia coli bacteria have been investigated. Additionally, the results obtained from in silico molecular docking studies confirm the interaction of nanocomposite with proteins, were in good agreement with the experimental data. This finding provides a novel and simple method for the synthesis of cellulose/TiO2 nanocomposite as functional biomaterials.